Enhancing Students’ Ability In Reading By Watching Movie - Junaidi Junaidi (Rahis Cendekia Indonesia, 2023)
This ponder pointed to know whether utilizing English subtitle in observing is successful or not in expanding students' lexicon in grade IX SMPN 1 Aek Natas. This considers is an exploratory ponder. The populace of this ponder is understudies in review IX comprising of 308 understudies. By utilizing purposive testing strategy, course D was chosen as exploratory gather with 31 understudies and class was chosen as control bunch with 31 understudies. Both bunches were given pre-test, treatment and post-test. Pre-test and post-test comprised of 20 questions, 10 questions of coordinating words and 10 questions of fill within the clear with kind of perusing content. The sort of test related to the educating fabric in review IX was story content since the motion picture was folktale motion picture. Surveying students' state of mind was required in related of K-13 educational programs since the school was as of now utilized K-13 educational modules. The information was analyzed quantitatively utilizing t-test. The result of t-test was 3.25 with t-table at 0.005 = 2.66028 and t-table at 0.001 = 3.23171 it implies that t-test is higher than the t-table and thus the utilize of English subtitle was compelling in expanding students' lexicon.